Effect of thermal radiation and chemical reaction on MHD flow of blood in stretching permeable vessel - Zigta, Binyam (Zielona Góra: Uniwersytet Zielonogórski)
This paper focuses on the theoretical analysis of blood flow in the presence of thermal radiation and chemical reaction under the influence of time dependent magnetic field intensity. Unsteady non linear partial differential equations of blood flow consider time dependent stretching velocity, the energy equation also accounts time dependent temperature of vessel wall and the concentration equation includes the time dependent blood concentration.
Keywords: stretching velocity; similarity transformations; time dependent magnetic field intensity; thermal radiation; chemical reaction